Cisatracurium dosing in a patient with hyperthermia. (2nd July 2019) - Lim, Jin; Cox, Jenna; Nguyen, Thai; Arya, Rohan
Abstract: Purpose: A case report involving varying cisatracurium dosing requirements in a hyperthermic patient undergoing prone ventilation who subsequently received active cooling as part of targeted temperature management is presented. Summary: Cisatracurium is known to be primarily metabolized via pH- and temperature-dependent Hofmann elimination. Previous reports in the literature described cases of decreased dosing requirements for both cisatracurium and its parent compound, atracurium, for patients in hypothermic states. While augmented atracurium dosing requirements in hyperthermic states have been reported, a literature search found no such reports concerning cisatracurium administration. In the case described here, a patient was initiated on cisatracurium for treatment of symptoms suggestive of acute respiratory distress syndrome (ARDS) and septic shock. An initial dosing requirement of 12 µg/kg/min (adjusted to a goal of 2–4 twitches per train-of-four monitoring) was needed to achieve adequate paralysis while the patient remained hyperthermic (a bladder temperature of 40.1°C). This cisatracurium infusion rate exceeded maximum reported and maximum institutional infusion rates (10 µg/kg/min). After initiation of cooling and lowering of the bladder temperature to 37.8°C, the cisatracurium rate requirement decreased to 5 µg/kg/min. Conclusion: A hyperthermic patient thought to have ARDS and septic shock required a high rate of cisatracurium infusion for adequate paralysis during mechanical ventilation. The cisatracurium did not appear to cause prolonged neuromuscular blockade.